Psychopathic Capture within Financial Capitalism: Albert Dunlap, Scott Paper, and Sunbeam Corporation - Boddy, Clive (University of Darussalam Gontor Press, 2025)
This paper aims to explore the concept of ‘psychopathic capture’ within shareholder capitalism by examining the rise and fall of Albert Dunlap, one of the most self-congratulatory and media-applauded heroes of 20th-century capitalism. A historical analysis via a literature review of academic commentary on Albert Dunlap was undertaken. Additionally, Dunlap’s writings, press coverage, and reports from journalists who interviewed Dunlap was examined. The findings of this research: Dunlap’s tenure as CEO at Scott Paper and then Sunbeam Corporation saw him actively decreasing and eliminating the means of production by closing factories and making thousands of people redundant across the USA and elsewhere. Rather than building long-term capital, he destroyed it and was praised to the point of hero worship by the financial sector and rewarded for his destructiveness. This current paper demonstrates that ‘psychopathic capture’ exists within capitalism. Dunlap was psychopathic in his attitudes and behavior, and he captured (took over) the leadership of Sunbeam Corporation for at least two years. The results were psychopathic in that wealth was destroyed; employees were ruthlessly devalued, abused, and bullied, careers were ended, and shareholders were eventually impoverished. This is the first paper to specifically examine Priels’ idea of ‘psychopathic capture’ in relation to a detailed example from organizational history.